THE USE OF SONGS IN LEARNING ENGLISH TO THE STUDENTS OF THE FIFTH GRADE IN SD 1 MUHAMMADIYAH BINJAI - Br. Barus, Sri Andania; Sibarani, Berlin; Sumarsih, Sumarsih (Universitas Negeri Medan, 2020)
The objectives of this study were to analyze the Use of Songs in Learning English to the Students of the Fifth Grade in SD 1 Muhammadiyah Binjai. This study would be a descriptive study, which analyze the use of English to teach English in SD Muhammadiyah 1 Binjai. This study would be conducted by using Descriptive Qualitative Design. Descriptive Qualitative Design was just like other types of qualitative research, these inquiries typically are efforts to understand poorly understood phenomena that do not lend themselves readily to quantification. The song is used in two ways in the teaching of English to the elementary students. In the first way, the teacher organize the procedure of using the song into five steps, they are (1) listening to the song, (2) singing the song, (3) asking the students to sing it in front of the class, (4) discussing about the song, (5) the teacher give the task to the students. Besides that, only three out of the nine reasons that teacher take into consideration in explaining why the teacher taught English by using song the way she did. The three reasons are (1) song is a means of teaching pronunciation, (2) teaching vocabulary, (3) making fun teaching situation.Keywords : Songs, Media, Teaching English, Teacher